Timing and rate of global contraction on Mercury - Kelsey T. Crane; Christian Klimczak (Geophysical Research Letters)
Abstract Impact bombardment and global contraction due to planetary cooling have both shaped the surface of Mercury over very long time scales. Landforms associated with these processes, i.e., impact craters and thrust fault‐related escarpments, and their mutual geologic relationships were analyzed to gain insight into the temporal relationships between the two. We assess stratigraphic relationships of ~6000 thrust fault‐related landforms with all 20 km diameter and larger craters to statistically evaluate the timing and rate of contraction on Mercury. Geometric probabilities were computed for thrust faults crosscutting craters of different degradation stages that correspond to different time‐stratigraphic systems, which allow determination of the onset and time derivative of global contraction. Results show that this process had begun after the late heavy bombardment of the inner solar system and likely gradually slowed toward the present. Implications arise for thermal history models as well as slip rates and quake recurrence intervals along thrust faults on Mercury.